Bioactivity and stability studies of anthocyanin-containing extracts from Garcinia mangostana L. and Etlingera elatior Jack - Sujatha Ramasamy,; Nor Afifa Mazlan,; Nurul Asyikin Ramli,; Wan Nur Asyiqin Rasidi,; Sugumaran Manickam, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Anthocyanin-containing extract (ACE) were prepared from the pericarp of Garcinia mangostana L. (mangosteen) and the inflorescence part of Etlingera elatior Jack (torch ginger) by using acidified methanol as extraction solvent. Our present study focuses on the antioxidant and cytotoxic activity and the effect of temperature, light and pH on stability of ACE derived from G. mangostana and E. elatior. The monomeric anthocyanin and total phenolic content in E. elatior was higher (43.42±0.01 mg/L dan 10.07±0.01 gGAE /100 g) compared to G. mangostana (15.03±0.01 mg/L and 3.29±0.01 gGAE/100 g). Both ACE of E. elatior and G. mangostana exhibited free radical scavenger activity, with IC50 value of14.90±1.02 mg/mL and 15.50±0.52 mg/mL, respectively, in 2,2’-diphenyl-1-picrylhydrazyl assay. ACE of E. elatior was also found to be a good reducing and possessed higher absorbance values at concentrations range from 1.25 to 20 mg/mL in FRAP assay. ACE of E. elatior exhibited mild cytotoxicity on human ovarian SKOV-3 cell line with IC50 values of 54.32 ± 4.60 μg/mL. The effects of light and temperature on ACE stability were performed in different environmental conditions, which promote the destabilization of anthocyanin molecules. ACE stability of G. mangostana were less resist to the effect of light but very susceptible to the prolonged effect of heat after 2 h exposure compared to the ACE in E. elatior. The different in pH highly influence the stability of both ACE which can be observed from the decrease in absorbance readings.